Jonge Plastiek uit België. (Maastricht : Bonnefantenmuseum, 1973)
Bailleux, Cesar ; Bonduel, Roger ; Cardon, Eric ; Decock, Gilbert ; Dries, Jan ; Koenraad ; Laenen, Jean-Paul ; Mestdagh, Roberte ; Van De Kerckhove, Jan ; Van Rafelghem, Paul ; Van Sumere, Hilde ; Verstockt, Mark
Jonge Plastiek uit België, Bonnefantenmuseum, Maastricht, 28 april t/m 27 mei 1973
boek
Keywords: België